Collaborating on ESG consulting, reporting, and communicating education: Using partner maps for capability building design - Liao, Han-Teng; Pan, Chung-Lien; Zhang, Yuan (Frontiers in Environmental Science, 2023)
Given the rising demand for environmental, social, and governance (ESG) talents, the study aims to provide a multi-disciplinary outlook of specific capability requirements of ESG talents focusing on the use of ESG and carbon information, thereby filling the literature gap in ESG education. Following the design science conventions and running design workshops that integrate design thinking of “how might we” design questions, literature analysis, and expert interviews across disciplines, the study presents findings regarding three main consulting, reporting, and communicating activities. Based on the iterations of design workshops that adopt a circular economy-based partner map design canvas for stakeholder analysis, with procedures including expert interviews and literature reviews, three Partner/Capability Maps were generated to map out the stakeholders and explore the capabilities needed. Digital and data skills using ESG and carbon information emerged as the core capability to complete all three tasks. A conceptual framework, Smart System on ESG and Carbon Information, is proposed to summarize the planning, operating, and engaging with ESG and carbon information, along with high-level organizational actions and talent capabilities. It identifies building blocks that amount to an ESG operating system within an enterprise, with the purpose to engage various stakeholders for value-creation collaboration. Despite the limitations in the lack of comprehensive review and limited geographic and disciplinary representation, the study provides a roadmap for enterprises and universities to explore and define talent requirements and create specific education and training programs.